Use of antipsychotics and risk of breast cancer: a Danish nationwide case–control study. (8th July 2018) - Pottegård, Anton; Lash, Timothy L.; Cronin‐Fenton, Deirdre; Ahern, Thomas P.; Damkier, Per
Abstract : Aims: Some antipsychotics increase prolactin levels, which might increase the risk of breast cancer. Existing evidence is conflicting and based on sparse data, especially for the increasingly used second‐generation antipsychotics. We conducted a nationwide case–control study of the association between antipsychotic use and incident breast cancer. Methods: From the Danish Cancer Registry, we identified women with a first‐time diagnosis of breast cancer 2000–2015 ( n  = 60 360). For each case, we age‐matched 10 female population controls. Using conditional logistic regression, we calculated odds ratios (ORs) for breast cancer associated with use of antipsychotics. We stratified antipsychotics by first‐ and second‐generation status and by ability to induce elevation of prolactin. Results: In total, 4951 cases (8.1%) and 47 643 controls (7.9%) had ever used antipsychotics. Long‐term use (≥10 000 mg olanzapine equivalents) was associated with breast cancer, with an adjusted OR of 1.18 [95% confidence interval (CI), 1.06, 1.32]. A weak dose–response pattern was seen, with ORs increasing to 1.27 (95% CI 1.01, 1.59) for ≥50 000 mg olanzapine equivalents. Associations were similar for first‐ and second‐generation antipsychotics (ORs 1.17 vs . 1.11), but also for nonprolactin inducing‐antipsychotics (OR 1.17). Stratifying by oestrogen receptor status, positive associations were seen for oestrogen receptor‐positive cancers (long‐term use: OR 1.29; 95% CI 1.13, 1.47) while no associations were observed for oestrogen receptor‐negative cancers. Conclusions: Overall, our results do not suggest a clinically important association between antipsychotic use and risk of breast cancer. The importance of drug‐induced prolactin elevation is unclear but may lead to a slightly increased risk of oestrogen receptor‐positive breast cancer.